A new early miocene penguin skull from patagonia: Taxonomic and paleobiological value - Acosta Hospitaleche, Carolina Ileana Alicia (2011)
In this work, a new skull (MLG 3400) exhumed from the Chenque Formation (early Miocene of Santa Cruz Province, Argentina) (Fig. 1) is assigned to Spheniscidae cf. Spheniscus Brisson, 1760 (Fig. 2). The significance of this finding is that it increases the penguin fossil record in the area, which is scant and consisting of only isolated remains.